An increasing number of convolutional neural networks for fracture recognition and classification in orthopaedics. (2021) - Carmo, L. Oliveira e; Merkhof, A. van den; Olczak, J.; Gordon, M.; Jutte, P. C.; Jaarsma, R. L.; IJpma, F. F. A.; Doornberg, J. N.; Prijs, J.
No abstract available